Optimal design of a composite laminate hydrogen storage vessel. (6th December 2012) - Lin, David T.W.; Hsieh, Jui‐Ching; Chindakham, Nachaya; Hai, Pham Duy; Hu, Yun Hang
SUMMARY The purpose of this study is to optimize the design of a composite laminate hydrogen storage vessel for minimizing stress concentration. The optimum design of this study uses the finite‐element method combined with a simplified conjugated gradient method (SCGM) and genetic algorithm (GA) to find the minimization of von Mises stress of the composite laminate hydrogen storage vessel. In this study, a composite laminate hydrogen storage vessel with an aluminum liner and a carbon fiber/epoxy layer are considered. The winding angle and thickness of the composite layer are proposed as optimal design variables. The comparison between SCGM and GA is discussed in order to obtain a promising optimum in design process. Through this optimization, the best possible combination of winding angle and thickness of composite layer has been obtained to obtain minimum possible stress concentration. Copyright © 2012 John Wiley & Sons, Ltd.